The impact of agricultural production diversity on farmer household dietary diversity: a case study of Nanjing City - Shen, Qi; Qiang, Tingting; Zhong, Taiyang (Frontiers in Nutrition, 2025)
Background/ObjectivesChina is one of the first developing countries to achieve poverty reduction goals, but there are still problems with unbalanced dietary structures in rural areas. The food consumption problem of rural residents is a major social issue that deserves attention, and food security should be guaranteed.MethodsThis paper takes rural households in Nanjing as the research object and uses feasible generalized least squares and simultaneous equation models to explore the relationship between the diversity of rural household production and dietary diversity in Nanjing and analyze the differences in the impact of production diversity and market purchases on dietary diversity and other related influencing factors.ResultsThe results show that agricultural production has changed from “small and comprehensive” with diversity to relatively single “specialization”. The higher the diversity of crop production of rural households, the higher their dietary diversity. The dietary diversity of rural households in Nanjing is relatively low, and their food consumption structure is unreasonable.ConclusionThe impact of production diversity and market purchases on dietary diversity is different, and the positive impact of production diversity on dietary diversity is greater than that of market purchases. Encouraging farmers to apply for agricultural product certification, cultivating new types of professional farmers, and expanding channels for selling agricultural products can effectively improve the dietary diversity of rural households.